ACTR-58. BASELINE REQUIREMENTS FOR NOVEL AGENTS BEING CONSIDERED FOR BRAIN CANCER EFFICACY TRIALS: REPORT OF AN ABTC WORKSHOP. (11th November 2019) - Grossman, Stuart; Romo, Carlos; Rudek-Renaut, Michelle; Supko, Jeffrey; Fisher, Joy; Nabors, Burt; Wen, Patrick; Peereboom, David; Ellingson, Benjamin; Ye, Xiaobu
Abstract: Despite advances in the understanding of molecular pathways, the availability of NGS panels to identify potentially drugable mutations, the proliferation of targeted therapies, and the progress seen in other cancers, only one novel agent (temozolomide) has significantly improved the survival of patients with glioblastoma in the past three decades. A major factor distinguishing brain cancer from other malignancies is the presence of the blood-brain barrier that restricts entry into the central nervous system of over 95% of drugs currently approved by the FDA. Clinical investigators have historically justified glioblastoma efficacy trials with pharmacokinetic data documenting measurable brain concentrations in animals or in contrast enhancing brain tumor specimens from patients. However, the discovery of effective therapeutic agents (whose mechanism of action requires that the drug directly reaches the cancer) will likely require that therapeutic drug concentrations (rather than measurable levels or blood:brain ratios) be delivered to non-contrast enhancing regions of the brain. The importance of delivering therapeutic concentrations of drug to non-enhancing brain is highlighted by knowledge that a gross total resection of all enhancing portions of a glioblastoma provides no chance of cure and limited improvement in overall survival. Utilizing these more stringent emerging criteria to select novel agents for efficacy studies will encourage pre-clinical and phase I studies to define the CNS penetration of new drugs and determine a therapeutic concentration for each agent. This will aid in the rational prioritization of agents selected for phase II studies. A full report of the outcome of the ABTC workshop on this topic will be presented. This will include: 1) methods to determine "therapeutic" drug concentrations for glioblastoma, 2) methods to quantify drug concentrations in non-enhancing brain, 3) pharmacokinetic and pharmacodynamic considerations, and 4) potential shortcomings of this approach.